Effect of Submaximal Exercise on Trained and Untrained Intensity on Estrogen Levels in Female White Rats (Rattus Norvegicus) Wistar Strains - Cinthya Fitri Paramitha; Mita Herdiyantini; Eric Mayo Dagradi; Annisa Ulya Rasyida (Universitas Wijaya Kusuma Surabaya, 2024)
Background: Trained and continuous physical activity can increase estrogen levels in women, while irregular activity can increase excessive Estrogen levels. Submaximal exercise is a recommended exercise to improve a woman's physiological function The purpose of this experiment was to determine the effect of submaximal exercise on trained and untrained intensity on Estrogen levels in female white rats (Rattus norvegicus) Wistar strains. Methods: This research was an experimental study using a post-test-only control group design using 30 female Wistar rats which were divided into 5 groups: control group not treated (K1), experimental group of animals with exercise intensity without intervention (K2), group of experimental animals with untrained intensity without intervention (K3), group of experimental animals with exercise intensity with intervention (K4), and experimental group of animals with exercise intensity with intervention (K4). experimental animals with untrained intensity treatment with intervention (K5). The intervention was swimming at moderate intensity with a duration of 85% of the maximum time to swim and a load of 8% of the rat's body weight. After the treatment period, all groups were terminated to take intracardiac blood measured using ELISA. Results: The data results were analyzed using statistical tests. The results of this study found that the trained group had lower Estrogen levels compared to the untrained group, but higher than the control group. The Kruskal-Wallis test show a significance value (p = 0.157), p> 0.05. Conclusion: In this study, there was no effect of submaximal exercise between trained and untrained intensity on Estrogen levels in Wistar strain female white rat.